Economic evaluation of a conditional cash transfer to retain women in the continuum of care during pregnancy, birth and the postnatal period in Kenya. - Tom Palmer; Neha Batura; Jolene Skordis; Oliver Stirrup; Fedra Vanhuyse; Andrew Copas; Aloyce Odhiambo; Nicholas Ogendo; Sarah Dickin; Alex Mwaki; Hassan Haghparast-Bidgoli (PLOS Global Public Health, 2022)
There is limited evidence on the cost and cost-effectiveness of cash transfer programmes to improve maternal and child health in Kenya and other sub-Saharan African countries. This article presents the economic evaluation results of the Afya trial, assessing the costs, cost-effectiveness and equity impact of a demand-side financing intervention that promotes utilisation of maternal health services in rural Kenya. The cost of implementing the Afya intervention was estimated from a provider perspective. Cost data were collected prospectively from all implementing and non-implementing partners, and from health service providers. Cost-efficiency was analysed using cost-transfer ratios and cost per mother enrolled into the intervention. Cost-effectiveness was assessed as cost per additional eligible antenatal care visit as a result of the intervention, when compared with standard care. The equity impact of the intervention was also assessed using a multidimensional poverty index (MPI). Programme cost per mother enrolled was International (INT)$313 of which INT$ 92 consisted of direct transfer payments, suggesting a cost transfer ratio of 2.4. Direct healthcare utilisation costs reflected a small proportion of total provider costs, amounting to INT$ 21,756. The total provider cost of the Afya intervention was INT$808,942. The provider cost per additional eligible ANC visit was INT$1,035. This is substantially higher than estimated annual health expenditure per capita at the county level of $INT61. MPI estimates suggest around 27.4% of participant households were multidimensionally poor. MPI quintiles did not significantly modify the intervention effect, suggesting the impact of the intervention did not differ by socioeconomic status. Based on the available evidence, it is not possible to conclude whether the Afya intervention was cost-effective. A simple comparison with current health expenditure in Siaya county suggests that the intervention as implemented is likely to be unaffordable. Consideration needs to be given to strengthening the supply-side of the cash transfer intervention before replication or uptake at scale.